Down-regulation of intestinal epithelial innate response by probiotic yeasts isolated from kefir - Romanin, David Emmanuel (2010)
Kefir is obtained by milk fermentation with a complex microbial population included in a matrix of polysaccharide and proteins. Several health-promoting activities has been attributed to kefir consumption. The aim of this study was to select microorganisms from kefir able to down-regulate intestinal epithelial innate response and further characterize this activity.Caco-2 cells stably transfected with a human CCL20 promoter luciferase reporter were used to screen a collection of 24 yeast and 23 bacterial strains isolated from kefir. The Toll-like receptor 5 agonist, flagellin was used to activate the reporter cells, while pre-incubation with the selected strains was tested to identify strains with the capacity to inhibit cell activation. In this system, 21 yeast strains from the genera Saccharomyces, Kluyveromyces and Issatchenkia inhibited almost 100% of the flagellin-dependent activation, whereas only some lactobacilli strains showed a partial effect. K. marxianus CIDCA 8154 was selected for further characterization. Inhibitory activity was confirmed at transcriptional level on Caco-2/TC-7 and HT-29 cells upon flagellin stimulation. A similar effect was observed using other pro-inflammatory stimulation such as IL-1β and TNF-α. Pre-incubation with yeasts induced a down-regulation of NF-κB signalling in epithelial cells in vitro, as well as expression of other pro-inflammatory chemokines such as CXCL8 and CXCL2. Furthermore, modulation of CCL20 mRNA expression upon flagellin stimulation was evidenced in vivo, in a mouse ligated intestinal loop model.Results indicate kefir contains microorganisms able to abolish the intestinal epithelial inflammatory response that could explain some of the properties attributed to this fermented milk.